2017
DOI: 10.1177/0893318917691358
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Communicative and Hierarchical Foundations of High Reliability Organizing in Wildland Firefighting Teams

Abstract: Organizational hierarchy is an inescapable aspect of many exemplary high reliability organizations (HROs). As organizations begin to adopt HRO theorizing to improve practice, it is increasingly important to explain how HRO principles-which assume the hallmarks of a flat hierarchy-can be understood and enacted in rigidly stratified organizations. We propose a preliminary theoretical model suggesting how various supervisorsubordinate and work group communication patterns and practices enable members to navigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Attempts to identify the processes that contribute to mindful high-reliability organizing focus on enacting five principles. These five principles, developed by Weick and Sutcliffe (2001, have become the most prominent model for delineating HRO effectiveness and pinpointing communicative processes that undermine these principles ( Jahn and Black, 2017). Each principle is comprised of a set of behaviors that promotes reliability, resilience, and safety.…”
mentioning
confidence: 99%
“…Attempts to identify the processes that contribute to mindful high-reliability organizing focus on enacting five principles. These five principles, developed by Weick and Sutcliffe (2001, have become the most prominent model for delineating HRO effectiveness and pinpointing communicative processes that undermine these principles ( Jahn and Black, 2017). Each principle is comprised of a set of behaviors that promotes reliability, resilience, and safety.…”
mentioning
confidence: 99%
“…As to organisational context, studies have demonstrated that information exchange about tasks within the group produce significant benefits to the group work’s own functioning (Jahn and Black, 2017). The importance of information in groups can be attested by the reduction of costs at work (Cummings, 2004), by positive effects on the outcome and in the group’s creativity abilities (Jehn and Bendersky, 2003) and by the development of organisational learning (Mallén et al , 2016).…”
Section: Theoretical Framework and Approach Of Hypothesismentioning
confidence: 99%
“…Thus, the interviews constituted a set of advice-givers to whom the reader is apt to listen. In addition, an analogy may be drawn between criterion case and case-based studies of high-reliability organizations (HROs; for example, Jahn & Black, 2017). Although rarely stated explicitly, studies of HROs assume that the organizational communication practices that emerge when human lives are at stake are nonnormative and honorable (Weick & Sutcliffe, 2015).…”
Section: Pdcs Strategiesmentioning
confidence: 99%